TeleNGAGE: Enhancing Collaboration Between Families and Schools - Katherine Curry; Ed Harris; Jentre Olsen; Younglong Kim; Dominic Egure (Arizona State University, 2023)
Findings in the literature strongly support the importance of family engagement in education. However, effective partnerships between families and schools are rare, especially in ethnically diverse communities where families may lack efficacy or face structural challenges for engagement. Additionally, educator perspectives toward engagement are often framed by White, middle-class paradigms. Educators often fail to acknowledge structural challenges faced by low-income families or the cultural contributions low-income and/or minoritized families can bring. To facilitate engagement between families and schools, a new ECHO® line, TeleNGAGE, was developed at Oklahoma State University, Educational Leadership program. ECHO®, traditionally used in the field of medicine, has utility for professional development for educators because it offers a platform for case-based learning where real problems are addressed in real-time. Additionally, didactic presentations provide professional development for collaborative learning. Through the lens of Communities of Practice (CoP), this qualitative case study explores how relationships between families and schools changed as a result of participation in TeleNGAGE. Tenets of CoP, negotiated meaning, mutual engagement, and a shared repertoire, support a collaborative approach to addressing complex problems. Findings suggest that a CoP has emerged through TeleNGAGE and has resulted in changes in perspectives across families and educational leaders about "what it means to be engaged," enhanced family efficacy for engagement, and changes in engagement practice as family voice has expanded through sharing of concerns/perspectives. These findings have important implications for equitable engagement in a convenient, cost-free environment where educators and families can communicate and develop mutually supportive understandings and practices.